2021
DOI: 10.1111/eci.13574
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐CoA‐driven respiration in frozen muscle contributes to the diagnosis of mitochondrial disease

Abstract: Background: Freezing human biopsies is common in clinical practice for storage.However, this technique disrupts mitochondrial membranes, hampering further analyses of respiratory function. To contribute to laboratorial diagnosis of mitochondrial diseases, this study sought to develop a respirometry approach using O2k (Oroboros Ins.) to measure the whole electron transport chain (ETC) activity in homogenates of frozen skeletal muscle biopsies. Patients and Methods: We enrolled 16 patients submitted to muscle bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To investigate whether NR supplementation improves mitochondrial respiration function in HFpEF mice, we measured mitochondrial respiratory capacity in HFpEF and NR-treated HFpEF mice using the Oroboros Oxygraph-2k based on the previously published protocol by Zuccolotto-dos-Reis et al. 38 Oxygen consumption rates in the energized state were found to be significantly higher in the NR-treated HFpEF mouse hearts as compared with HFpEF mouse hearts ( Figures 5F and 5G ), suggesting an increased mitochondrial respiration rate and ATP generation in HFpEF mice treated with NR.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether NR supplementation improves mitochondrial respiration function in HFpEF mice, we measured mitochondrial respiratory capacity in HFpEF and NR-treated HFpEF mice using the Oroboros Oxygraph-2k based on the previously published protocol by Zuccolotto-dos-Reis et al. 38 Oxygen consumption rates in the energized state were found to be significantly higher in the NR-treated HFpEF mouse hearts as compared with HFpEF mouse hearts ( Figures 5F and 5G ), suggesting an increased mitochondrial respiration rate and ATP generation in HFpEF mice treated with NR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, including in the Oroboros Oxygraph-O2k 27 , have presented methods to assess the oxygen consumption of the electron transfer system from cryopreserved samples 21,22 . Through consideration of these studies, we have developed the methods reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Titration of rotenone demonstrates the succinate-only sustained respiration. Previous studies, including in the Oroboros Oxygraph-O2k [26], have presented methods to assess the oxygen consumption of the electron transfer system from cryopreserved samples [21,22]. consideration of these studies, we have developed the methods reported in this study.…”
Section: Plos Onementioning
confidence: 99%